Evaluation of stress distribution in an endodontically treated tooth restored with four different post systems and two different crowns- A finite element analysis - Rajvi Nahar; Sunil Kumar Mishra; Ramesh Chowdhary (Journal of Oral Biology and Craniofacial Research)
Aim and objectives: The study evaluated the stress distribution in an endodontically treated tooth with four different post systems and restored with two different prosthetic crown materials using finite element analysis (FEA). Material and methods: A total of eight 3D FEA models of maxillary central incisor were created and divided into two groups; group porcelain fused to metal (PFM) crown (n = 4) and group PEEK crown (n = 4). The endodontically treated tooth was restored using four different post materials such as fiber-reinforced composite (FRC), carbon fiber-reinforced polyetheretherketone (CFR-PEEK), glass fiber reinforced polyetheretherketone (GFR-PEEK) and polyetherketoneketone (PEKK) and composite resin core. A static load of 100 N was applied and von Mises stress was calculated. The stress ratio in dentin was analyzed by using the Mohr-Coulomb failure theory. Results: In dentin, under the applied forces for both, PFM group and PEEK group, it was observed that CFR-PEEK post exhibited minimum von Mises stress while PEKK post exhibited maximum von Mises stress values. The result obtained showed that low stresses were detected using CFR-PEEK post than FRC, GFR-PEEK, and PEKK posts. Conclusion: Stress observed in dentin, when CFR-PEEK post was used was lesser in comparison to the FRC post. It was noted that PEEK crown and the PFM crown showed similar effect in dentin in stress generation. Hence, PEEK crown can be used as an alternative to the PFM crown.